Factors associated with delay or avoidance of medical care during the COVID-19 pandemic in Armenia: results from a nationwide survey - Serine Sahakyan; Diana Muradyan; Aida Giloyan; Tsovinar Harutyunyan (BMC, 2024)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic has disrupted healthcare systems throughout the world. Many patients faced delays and cancellation of care due to scaled back services, mobility restrictions, and concerns related to the risk of infection. The present study aimed to assess the prevalence of and risk factors associated with the avoidance or delay of medical care due to COVID-19 in Armenia. Methods We conducted a cross-sectional telephone survey of 3,483 adults across Armenia. We used stratified two-stage cluster sampling to select the participants from different age groups proportionate to their size in the population. Logistic regression analysis assessed the association of risk factors with avoidance/delay of routine, urgent/emergency, and any medical care. Results The mean age of the sample was 49.5 (SD = 14.8), ranging from 18 to 90. About 9.9% of the respondents avoided/delayed any type of medical care; whereas 5.5% avoided/delayed urgent/emergency care and 6.6% routine care. In the adjusted analysis, female gender and higher monthly expenditures were associated with avoidance/delay of routine medical care. Factors associated with delay/avoidance of urgent/emergency care included female gender and higher perceived threat of COVID-19. Younger age, female gender, higher perceived threat and not being vaccinated against COVID-19 were associated with avoidance/delay of any medical care in the adjusted analysis. Conclusion Since avoiding or delaying care might increase morbidity and mortality associated with conditions not related to COVID-19, identifying population groups that are more likely to avoid care is important. Targeting such groups with educational interventions focusing on the risks of using versus not using medical care in times of pandemic might be crucial. Ensuring the provision of in-home healthcare services for high-risk groups might help to address important medical care needs during the pandemic.